1994
DOI: 10.1172/jci117135
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic induction of interleukin-8 gene expression in human endothelial cells.

Abstract: Because leukocyte-mediated tissue damage is an important component of the pathologic picture in ischemia/reperfusion, we have sought mechanisms by which PMNs are directed into hypoxic tissue. Incubation of human endothelial cells (ECs) in hypoxia, Po2 -14-18 Torr, led to time-dependent release of IL-8 antigen into the conditioned medium; this was accompanied by increased chemotactic activity for PMNs, blocked by antibody to IL-8. Production of IL-8 by hypoxic ECs occurred concomitantly with both increased leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
161
4
6

Year Published

1996
1996
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 322 publications
(181 citation statements)
references
References 38 publications
10
161
4
6
Order By: Relevance
“…Indeed hypoxia exposure whether, in vitro or in vivo, is associated with rise in inflammatory markers. However, in the previous studies, as also quoted in the article by the authors, the duration of hypoxia exposure varied from 16 to 72 h [2][3][4][5] On the contrary, in the present study duration of simulated hypoxia of 4500 m was only 30 min. It remains obscure that those changes seen in the chemokines are actually the result of hypoxia induced inflammation or otherwise.…”
Section: To the Editorcontrasting
confidence: 51%
“…Indeed hypoxia exposure whether, in vitro or in vivo, is associated with rise in inflammatory markers. However, in the previous studies, as also quoted in the article by the authors, the duration of hypoxia exposure varied from 16 to 72 h [2][3][4][5] On the contrary, in the present study duration of simulated hypoxia of 4500 m was only 30 min. It remains obscure that those changes seen in the chemokines are actually the result of hypoxia induced inflammation or otherwise.…”
Section: To the Editorcontrasting
confidence: 51%
“…It is also possible that in vivo in¯ammatory cells such as microglia or macrophages participate in IL-8 expression since anoxia can stimulate them to release IL-8 (Metinko et al, 1992). Tumor microvascular cells were not found to express IL-8, although endothelial cells can synthesize IL-8 in response to hypoxia (Karakurum et al, 1994;Stevens and Rodman, 1995;Ziesche et al, 1996). Despite the fact that hypoxia stimulates the release of IL-8 and facilitates polymorphonuclear leukocytes (PMN) transmigration (Colgan et al, 1996), PMN in®ltrates are rarely found in glioblastoma sections.…”
Section: Discussionmentioning
confidence: 99%
“…1 Immunosuppressants, acute graft-versus-host disease (GVHD), viral infection, and steroids have been reported as possible risk factors for secondary clinical manifestations of TMA after BMT, but the pathogenesis is still unknown. [2][3][4][5][6] However, some information concerning possible secondary clinical manifestations of TMA [7][8][9][10] and an association between vascular endothelium damage and increased levels of cytokines 11 as well as chemokines 12,13 has been reported.…”
Section: Cular Endothelial Damagementioning
confidence: 99%